Scientific center “Express” of the JSC “VNIIZHT”: history and modernity - E. A. Zubkova; T. A. Karpeeva (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
The article reflects the most important areas of work of scientists and employees of the scientific center “Express” and their contribution to the formation and development of information technology since the founding in 1959 of the Department of computer science of the All-Union Scientific Research Institute of Railway Transport and up to the present.Theoretical foundations of the application of transport cybernetics in the national economy of the country were created by Corresponding Member of the Academy of Sciences of the USSR A. P. Petrov, who was one of the first to use mathematical methods and computing technology in solving transport problems and headed the development in this direction at the institute. The practical work on the creation of the first domestic automated system for selling tickets for trains, called “Express”, was headed by B. E. Marchuk.Since then, the “Express” system has transformed from a local ticketing system at the Kievsky railway terminal in Moscow into a powerful multifunctional international passenger traffic management system that interacts with the ticket reservation systems of European countries.Theoretical and practical developments carried out by the scientific center have resulted in the introduction of new information technologies in the Russian Railways holding and in the railway administrations of the member states of the Commonwealth.At present, the main activities of the staff of the scientific center are the creation of automated control system “Express” of a new generation (ACS “Express” NP) and the system of international integration of passenger transportation Express International.